Chemical warfare in termites - Sobotník, Jan; Jirosová, Anna; Hanus, Robert (Journal of insect physiology, 2010)
The rapid development of analytical methods in the last four decades has led to the discovery of a fascinating diversity of defensive chemicals used by termites. The last exhaustive review on termite defensive chemicals was published by G.D. Prestwich in 1984. In this text, we aim to fill the gap of the past 25 years and overview all of the relevant primary sources about the chemistry of termite defense (126 original papers, see Fig. 1 and online supplementary material) along with related biological aspects, such as the anatomy of defensive glands and their functional mechanisms, alarm communication, and the evolutionary significance of these defensive elements.
Keywords: Isoptera; komunikace zvířat; Behavior, Animal; chování zvířat; Animal Communication; Biological Evolution; Animals; biosyntetické dráhy; Biosynthetic Pathways; biologická evoluce; Diterpenes; diterpeny; zvířata